(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
Recent medical advances and subsequent law reform in the United Kingdom have reignited debate about the ethics of mitochondrial DNA donation and transfer. The potential personal and societal benefits of permitting such practices must be considered against the ethical issues raised by them. It is argued that each objection is defeasible, assuming that safety and efficacy issues can be resolved. A brief description of the new provisions in the UK is provided.